Benchmark of the extension of frozen-density embedding theory to nonvariational correlated methods: the embedded-MP2 case - Sen, Reena; Gonzalez-Espinoza, Cristina E.; Zech, Alexander; Dreuw, Andreas; Wesolowski, Tomasz A. (Journal of chemical theory and computation, 2021)
The extension of the frozen-density embedding theory for nonvariational methods [J. Chem. Theory Comput. 2020, 16, 6880] was utilized to evaluate intermolecular interaction energies for complexes in the Zhao-Truhlar basis set. In the applied method (FDET-MP2-FATLDA), the same auxiliary system is used to evaluate the correlation energy by means of the second-order Moller-Plesset perturbation theory (MP2), as in our previous work [J. Chem. Phys. 2019, 150, 121101]. Local density approximation is used for E-xcT(nad)[rho(A), rho(B)] in both cases. Additionally, the contribution to the energy due to the neglected correlation potential was evaluated and analyzed. The domain of applicability of the local density approximation for E-xcT(nad)[rho(A), rho(B)] was determined based on deviations from the interaction energies from the conventional MP2 calculations. The local density approximation for E-xcT(nad)[rho(A), rho(B)] performs well for hydrogen- or dipole-bound complexes. The relative errors in the interaction energy lie within 330%. While for charge-transfer complexes, this approximation fails consistently, and for other types of complexes, the performance of this approximation is not systematic. The sources of error are discussed in detail.